“It seems enormously valuable to me.” Perspectives of Dutch (potential) carriers of genetic FTD on onset-predictive biomarker testing - Charlotte H. Graafland; Harro Seelaar; Jessica L. Panman; Lize C. Jiskoot; Tjitske Kleefstra; Jackie M. Poos; Edo Richard; Maartje H.N. Schermer; John C. van Swieten; Laura Donker Kaat; Eline M. Bunnik (Alzheimer’s Research & Therapy)
Abstract Background Onset-predictive biomarker tests (OPBT) in genetic frontotemporal dementia (FTD) may be used to recruit mutation carriers into preventive clinical trials before symptoms manifest. This would require disclosure of OPBT results to potential participants. This study investigates the perspectives of Dutch presymptomatic mutation carriers and individuals at 50% risk of genetic FTD on disclosure of OPBT results. It focuses on their willingness to receive OPBT results, what impacts they foresee from disclosure, and their preferences for the process of disclosure. Methods Semi-structured interviews were conducted with presymptomatic mutation carriers and individuals at 50% risk of developing genetic FTD (n = 25), who had received genetic counselling or participate in a longitudinal cohort study. The interview transcripts were analysed using thematic inductive analysis. Results Main themes were: willingness to undergo biomarker testing, foreseen impact of test results, preferences regarding biomarker test features, and understanding of biomarker testing. Most participants would be willing to receive OPBT results in the context of clinical trial recruitment. Participants would also be willing to receive OPBT results without access to clinical trial participation, as they perceived utility from these results. They would use positive OPBT results to prepare for the future, e.g. by planning for care, drawing up advance care directives, retiring early, and spending final healthy years well. At the same time, they thought positive OPBT results might also have negative psychological impacts on self-image or social dynamics with others. Implications of positive OPBT results for self-image as healthy or ill differed between participants. Negative OPBT results would provide relief and not lead to life changes. Conclusions Dutch presymptomatic mutation carriers and individuals at 50% risk of developing genetic FTD tend to be willing to receive OPBT results. The results would allow for participation in a clinical trial and preparation for onset through personal life planning. At the same time, disclosure of OPBT results might have negative psychological consequences. This study provides valuable input for developing ethical guidance and an appropriate counselling process to ensure responsible disclosure of OPBT results with clinical trial recruitment.